UPAYA KEPALA SEKOLAH DALAM MENINGKATKANMUTU GURU PENDIDIKAN AGAMA ISLAM (STUDI KASUS DI SMA NEGERI 1 KOLAKA) - irfan, Muh; Hartono, Hartono; Kasmiah, Kasmiah (IAI Al-Mawaddah Warrahmah Kolaka, 2020)
SMA Negeri 1 Kolaka, one of the referral schools in the district. Kolaka has a number of students and teachers who are very supportive of intelligent and quality human resources. The researcher saw that the teachers of Islamic Education at SMA Negeri 1 Kolaka had a bachelor's degree in education who had pedagogical competence and professional competence and used teaching methods that made students more active in participating in learning. The purpose of this study was to describe the Principal's Efforts to Improve the Quality of Islamic Religious Education Teachers at SMA Negeri 1 Kolaka and to determine the Constraints and Solutions in Improving the Quality of Islamic Religious Education Teachers. The research method used is a descriptive type of research with a qualitative approach with the subject of the Principal and Teachers of Islamic Religious Education and Students. Then the research procedure carried out included intensive observation (observation, documentation, and interviews) of the Principal's Efforts to Improve the Quality of Islamic Education Teachers at SMA Negeri 1 Kolaka. The results of this study are as follows: a) Programming the MGMP activities of Islamic Religious Education teachers. B. Carry out supervision activities in schools, c. Supporting training, workshop and education and training activities, d) Encouraging teachers to continue their education. The constraints and solutions are as follows: Constrained from funds, Lack of participants for each training activity, PAI teachers have not been fully active in studying the 2013 Curriculum material, PAI teachers have not applied the 2013 curriculum in the teaching and learning process, PAI teachers are still not maximally using media in the process teaching and learning and the completeness of learning tools before entering teaching. The solution is that the principal allocates special funds to teachers for each activity, programmed each PAI teacher to participate in training activities, provided follow-up that further improved teacher quality and Notified teachers to always actively learn and apply the 2013 curriculum and use Information Technology in the teaching and learning process